Evaluating the Guimar\~aes 2012 European Capital of Culture: a tourist perception approach - Paula Remoaldo; José Santos; Laurentina Vareiro; José Cadima Ribeiro (European Regional Science Association (ERSA), 2013)
The evaluation of the European Capitals of Culture (ECOC) by external entities has become a requirement after the Decision n. 1622/2006/EC of the European Commission. Simultaneously, as festivals, fairs and international exhibitions, and sporting mega events were taking an increasingly important role in the development of cities, regions and countries, the number of impact studies increased significantly. Evaluation is a multidimensional concept that should include not only economic, but also social, environmental, and cultural impacts. Guimar\~aes, in the Northwest of Portugal, has hosted, during the year 2012, one of the ECOC, and, as such, the opportunity to evaluate the impacts of this cultural event emerged. The approach used in the present paper to assess the success of the 2012 Guimar\~aes ECOC is the one of tourists, and their perception towards the city and the several realizations that took place during that year. Multiple studies have been made about the impact of mega events but fewer have focused on tourists as external and independent stakeholders, specifically on the evaluation of the activities of the European Capitals of Culture. with that aim, we undertook a survey, applied between August and September 2012, to 391 tourists that visited the city of Guimar\~aes, of which 390 were properly completed and provided usable data. The questionnaire was administered in some symbolic sites of the city, such as the castle of Guimar\~aes and the ?Duques de Bragança? palace (Paço dos Duques de Bragança), following the criteria of nationality to attain a random stratified sample. To explore the data from the survey, some t tests a factor analysis were used. The results show that hosting the 2012 ECOC was a major contribution for attracting new visitors to the city, although many of them went there just for a short period of time. The main source of general information collected by tourists was the Internet, and the traditional media. Only a small amount of respondents demonstrated a specialized knowledge of the cultural program. The most cited and appreciated performances came from the areas of music, exhibitions, and theatre. According to the perceptions of tourists, the tangible assets were clearly detached from the set of attributes of Guimar\~aes, including buildings, churches and chapels, whereas intangible assets were less noted. Overall, Guimar\~aes received a very positive evaluation related to city image and stay and is highly recommended by tourists to friends and relatives. The result of this research can be useful to managers interested in the planning and organization of future cultural events.
Keywords: 330; European Capital of Culture; Evaluation of Mega Events; Cultural Tourism; Guimar\~aes